2020
DOI: 10.3389/fmicb.2020.00628
|View full text |Cite
|
Sign up to set email alerts
|

Early and Short-Term Interventions in the Gut Microbiota Affects Lupus Severity, Progression, and Treatment in MRL/lpr Mice

Abstract: There have been attempts to reveal the possible associations between systemic lupus erythematosus (SLE) and gut microbiota. Using MRL/lpr mice, this study was performed to reveal whether early and short-term interventions in gut microbiota affect lupus. MRL/lpr mice were treated with antibiotics or fecal microbiota transplantation (FMT) before onset. Then, prednisone was used to treat the lupus mice with initially different gut microbiota compositions. The compositions of gut microbiota were assessed by the V3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Similarly, Zhang et al. showed that antibiotic treatment exacerbated the disease in MRL/lpr mice, possibly due to a short course and insufficient dose of antibiotics before lupus onset ( 31 ). Alternatively, another study found that vancomycin treatment ameliorated lupus symptoms in common MRL/lpr mice, but aggravated lupus in pregnant and postpartum (PP) mice.…”
Section: Potential Therapy For Sle: Modulating Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al. showed that antibiotic treatment exacerbated the disease in MRL/lpr mice, possibly due to a short course and insufficient dose of antibiotics before lupus onset ( 31 ). Alternatively, another study found that vancomycin treatment ameliorated lupus symptoms in common MRL/lpr mice, but aggravated lupus in pregnant and postpartum (PP) mice.…”
Section: Potential Therapy For Sle: Modulating Gut Microbiotamentioning
confidence: 99%
“…However, another study showed that treatment with antibiotics has no significant effect on both the gut microbiota and SLE progression in NZB/WF1 lupus mice, the mechanism of which is unclear (91). Similarly, Zhang et al showed that antibiotic treatment exacerbated the disease in MRL/lpr mice, possibly due to a short course and insufficient dose of antibiotics before lupus onset (31). Alternatively, another study found that vancomycin treatment ameliorated lupus symptoms in common MRL/lpr mice, but aggravated lupus in pregnant and postpartum (PP) mice.…”
Section: Oral Antibiotic Therapymentioning
confidence: 99%
“…The gut microbiota affects not only the activity of lupus but also the treatment effects of lupus with glucocorticoids [ 12 , 22 ]. At the same time, one of the mechanisms of GCs is regulating the gut microbiota to play the therapeutic effect [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota inhabits the intestine, forming a complex ecological community that influences normal physiology and susceptibility to disease through its collective metabolic activities and host interactions [ 11 ]. In the treatment of SLE by GCs, gut microbiota not only affects its efficiency but also serves as a therapeutic target [ 12 , 13 ]. However, little is known about whether gut microbiota plays role in the side effects of GCs in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL‐35 is capable of promoting the production of IL‐10 by B cells 75 . Recently, a study found that the frequency of IL‐35 + Bregs is reduced during SLE development, 76 whereas other studies revealed a low diversity of gut microbiota in the SLE mouse model 77,78 . Thus, the reduction in IL‐35‐producing B cells in SLE is likely closely related to gut microbiota dysbiosis.…”
Section: Microbiota and B‐cell Functionmentioning
confidence: 99%